2008
DOI: 10.1021/jp710362r
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Gas Molecules Using Flexible and All-Carbon Nanotube Devices

Abstract: Carbon nanotubes (CNTs) are extremely sensitive to the electronic perturbations from environmental gases. However, the electrical detection of carbon monoxide (CO) is still a challenge. Here we show that 1 ppm of CO can be electrically detected at room temperature using a CNT resistor and the detection is proposed related to the sidewall functionalities (COOH). A simple all-CNT electronic nose composed of two resistors (or one resistor plus one transistor) is able to differentiate CO and other oxidative gases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 23 publications
2
66
0
Order By: Relevance
“…Sensors without iron porphyrin-both pristine (not shown) and functionalized (black curve) SWCNTsshowed negligible responses to CO, which was consistent with the previous reports. [18][19][20]27] Sensors with iron porphyrin showed dosimetric responses indicating irreversibility over the experimental time frame. Pristine SWCNTs (lacking the 4-pyridyl anchor group) when treated with Fe(tpp)ClO 4 (green curve) showed a modest response (−0.57 ± 0.09%).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensors without iron porphyrin-both pristine (not shown) and functionalized (black curve) SWCNTsshowed negligible responses to CO, which was consistent with the previous reports. [18][19][20]27] Sensors with iron porphyrin showed dosimetric responses indicating irreversibility over the experimental time frame. Pristine SWCNTs (lacking the 4-pyridyl anchor group) when treated with Fe(tpp)ClO 4 (green curve) showed a modest response (−0.57 ± 0.09%).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…[8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles. [24] Alternatively, nonchemiresistive examples of SWCNT CO detectors rely on other mechanisms including changes in capacitance [25] and resonant frequency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carboxylic acid group and defect sites may be formed on SWNT sidewalls as a result of purification steps, and interaction with CO molecules likely occurred. 20 Consequently, the COOH functionality and defect sites may play a key role in CO detection, resulting in a decrease in the electrical resistance of CNTs, despite the interaction with the holedonating gas. The CO sensing mechanism of PANI is not yet clear, but two plausible explanations have been proposed.…”
Section: Methodsmentioning
confidence: 99%
“…In 2000, Dai and co-workers demonstrated the potential of SWCNT-based gas sensor to NO 2 and NH 3 at room temperature [8], which inspired researchers to widely explore CNTs for gas sensors. SWCNTs have been considered promising candidates for gas sensing applications, which can detect toxic gases, such as NO 2 , NH 3 , O 2 , H 2 , CO 2 and CO [11][12][13]. Recently, in order to improve the sensing performance of these SWCNT-based sensors, many sensing materials such as conducting polymers [14,15], metals [16], and metal oxides [17] have been anchored on the surface of SWCNTs, and play important roles in the improvement of the sensitivity and selectivity of the resultant gas sensors.…”
Section: Introductionmentioning
confidence: 99%